Analysis of the Impact of Stock Prices and House Price Fluctuations on Resident Consumption in China - Hu, Huichu; Yifan Lei (International Theory and Practice in Humanities and Social Sciences, 2025)
The relationship between stock prices, house prices and resident consumption has long been a focus of the financial research with changes having an impact on the country’s macroscopic stability and fiscal stability, as well as affecting some economic activities to some extent. Research has found that there is a significant wealth effect of stock price and house price fluctuations on resident consumption. The theoretical analysis of the effects of stock price and house price fluctuations on resident consumption is presented in this paper. In addition, an empirical analysis of the effects of house price and stock price fluctuations on resident consumption is conducted based on regression analysis using quarterly data from 2013 to 2021. The results show that the negative crowding-out effect of stock prices and house prices on resident consumption is weaker than the positive boosting effect and the positive effect of stock prices on resident consumption is slightly weaker than that of house prices. Although the resident consumption is significantly affected by fluctuations in stock prices and house prices in the short term, the resident income is still the main influencing factor and driving force of resident consumption in the long term.